Hermite-Hadamard-Fejér type inequalities for convex functions via fractional integrals - İȘCAN, İmdat (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
In this paper, firstly we have established Hermite-Hadamard-Fejér inequality for fractional integrals. Secondly, an integral identity and some Hermite-Hadamard-Fejér type integral inequalities for the fractional integrals have been obtained. The some results presented here would provide extensions of those given in earlier works. Mathematics Subject Classification (2010): 26A51, 26A33, 26D10.